Coastline changes in mainland China from 2000 to 2015. (2nd January 2022) - Zhang, Ying; Qiao, Qinghua; Liu, Jia; Sang, Huiyong; Yang, Dazhi; Zhai, Liang; Li, Ning; Yuan, Xiaohui
ABSTRACT: The coastline is an indicator line for human exploitation in the coastal zone. With the acceleration of human development and climate change, changes in the coastal zone are more active than ever. Quickly extracting the coastline and monitoring its changes in real time is of great significance for enacting the development and utilisation planning of coastal zones. In this research, we developed an automatic-coastline-extraction technique based on edge detection and object-oriented in complex situations. Meanwhile, on the basis of Landsat TM images, it realised the extraction of the mainland China coastline. Accuracy comparison showed that the matching commission and omission errors between the extracted and reference coastlines within two-pixel radii were 8% and 5%, respectively. The Overall quality reached as high as 87%, achieving an overall mapping accuracy of 1:250, 000. We also constructed the index system of coastline exploitation and utilisation to analyse changes of the continental coastline from 2000 to 2015. It was found that natural and economic conditions affected coastline changes, in which the sea-expansion trend of northern China was more concentrated on a larger scale and with a higher load in coastline development and utilisation, while the southern region of China was relatively stable.